Flexural and Thermo-Mechanical Properties Assessment of Nano-Silica BFRPC and GFRPC - Muslim, Mohamad Asrofi; Jumahat, Aidah; Abdullah, Shahrul Azam; Kamaruzzaman, Fairuzzaman; Haris, Nurul Ain; Jaafar, Mohd Azrul; Raymond Siew Teng Loy (International Journal of Sustainable Construction Engineering and Technology, 2024)
Composite material is a high-performance material widely used in various applications, such as lorry boxes, due to their lightweight, high-strength properties, high chemical resistance and thermal stability. This study aims to evaluate the effect of Nano Silica Silane Treated (NS) inclusion on flexural behaviour and Dynamic Mechanical Analysis (DMA) properties of Glass/Basalt Fibre Reinforced Polymer (G/BFRP). Twelve composite systems were designed and fabricated using hand lay-up and vacuum silicon mould. Woven Basalt and Woven Glass Fibre were used as reinforcement materials. The polyester was modified with 1, 3, and 5 wt.% of Silane Treated Nano Silica (NS) using a mechanical stirrer before fabricated. The size samples of 80 x 13 x 5 mm for the flexural test and 40 x 10 x 5 mm for DMA were prepared and tested according to ASTM D790 and ASTM D5023-15. The results showed that adding NS as a filler in BFRP and GFRP enhanced the flexural and DMA behaviour. The highest flexural strength was found in 1wt%NS-BFRPC, with a value of 286.86 MPa. The GFRPC system tends to have slightly higher damping factors than the BFRC system. This indicates that the GFRPC system has a slightly higher ability to absorb energy and exhibit damping behaviour. This information can be valuable for designing composite materials for high-stiffness and strength applications.